(untitled) (Bangladesh Journal of Zoology, 2024)
In this study, we attempted species-level identification of frog specimen collected from Faridpur district of Bangladesh beyond it’s location outside Orissa, India. Specimen was identified morphologically at genus level as Fejervarya sp. belonging to the family Dicroglossidae using finger formula F3>F4>F1=F1 where F denote as toe finger. From the study two nucleotide sequences of 16S and 12S rRNA genes were obtained which contained 508bp and 408bp respectively. The Sequences were submitted to Gene Bank database with the accession number OQ231604 and OQ240197 for 16S and 12S rRNA gene sequences. Furthermore, the 16S rRNA gene sequence was used as molecular bar-code for the identified Orissa frog F. orissaensis species from Bangladesh. GC content of partial 12S and 16S rRNA genes have been calculated as 44% and 45% respectively. For 16S rRNA gene sequence there was no intra specific divergence. Whereas the inter specific polymorphic divergence were calculated 4.13% and 6.3% when the collected Orissa frog F. orissaensis was compared with that of F. iskandari and F. kupitzi, respectively. In case of 12S rRNA gene intra specific divergence was found 2.45% where the inter specific divergence were 4.41% and 6.86% when the collected Orissa frog F. orissaensis was compared with that of F. iskandari and F. limnocaris, respectively. Maximum likelihood tree also indicates that our sample Orissa frog formed a monophyletic group with F. orissaensis in both the cases of 16S and 12S rRNA genes and thus can be concluded as closely related. Therefore, the collected specimen was identified to be belonging to Fejervarya orissaensis which would be first report from Bangladesh outside Orissa, India. Bangladesh J. Zool. 51(3): 301-313, 2023